Sidney Chambers and the dangers of temptation - Runcie, James, 1959- (Runcie, James, 1959- Grantchester mysteries, 2016)
It's the summer of love in the late 1960s. The Apollo 11 astronauts are preparing to land on the moon, the war in Biafra dominates the news and Basil D'Oliveira has just been dropped from the England cricket team before a test series in apartheid South Africa. In the midst of all this change, Sidney Chambers, the loveable English clergyman, continues his amateur sleuthing investigations. A bewitching divorcee enlists Sidney's help in convincing her son to leave a hippie commune' at a soiree on Grantchester Meadows during May Week celebrations, a student is divested of a family heirloom; Amanda's marriage runs into trouble; Sidney and Hildegard holiday behind the Iron Curtain; Mrs. Maguire's husband returns from the dead; and an arson attack in Cambridge leads Sidney to uncover a cruel cast of blackmail involving his former curate. In the rare gaps between church and crime, Sidney struggles with a persistent case of toothache, has his first flutter at the Newmarket races, and witnesses the creation of a classic rock song. Charming, witty, intelligent, and filled with a strong sense of compassion, these six new stories are guaranteed to satisfy and delight this clerical detective's many fans.